Structural, electrical and optical properties of lanthanum-doped barium stannate. Issue 2 (March 2015) - Luo, B.C.; Zhang, J.; Wang, J.; Ran, P.X.
Abstract: Ba1− x La x SnO3 compounds were prepared by a conventional solid-state reaction method and their structural, electrical and optical properties were analyzed in this work. X-ray diffraction investigations revealed that La substitution in BaSnO3 led to the increase of cubic lattice parameters, whereas secondary phase appeared at x =0.1 or above. Evidences of the Sn 4+ state and oxygen vacancies were clearly observed in X-ray photoelectron spectroscopy. The semiconductor behavior in temperature-dependent resistivity was found to obey the variable-range hopping conduction mechanism. With the help of absorption spectra, smaller band-gap energy and larger Urbach tail energy were observed in Ba0.93 La0.07 SnO3, as compared with Ba0.97 La0.03 SnO3, which was discussed in the frame of the role of structural disorder.